Upaya Guru dalam Melatihkan Kedisiplinan Ibadah Siswa di MIS Bidayatul Hidayah 3 Medan Amplas - Harahap, Nur Saida; Matsum, Hasan (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2023)
The background of this study is the lack of self-awareness of students in worship discipline. This study aims to determine the efforts of fiqh teachers in training student worship discipline at MIS Bidayatul Hidaysh 3 Medan Amplas which includes the efforts of fiqh teachers to become uswatun hasanah, providing advice, punishments and rewards, training or practice and habituation as well as to find out the supporting factors and inhibiting factors of fiqh teachers' efforts in training worship discipline consisting of internal factors, namely awareness, interests, motivations, and mindsets, and external factors, namely habituation, parental example, school environment, and friends. This research uses a type of field research with a qualitative approach. The subject in this study was 1 teacher of jurisprudence subjects MIS Bidayatul Hidayah 3 Medan Amplas, while the object of this study was the efforts of fiqh teachers, supporting factors and inhibiting factors of fiqh teachers' efforts in training student worship discipline at MIS Bidayatul Hidayah 3 Medan Amplas. Data collection techniques are taken by observation, interviews and documentation. After the data is collected, it is then processed through data reduction, data presentation, and conclusions. Based on the results of the study, the efforts of jurisprudence teachers in training student worship discipline in Mis Bidayatul Hidayah 3 Medan Amplas are to be uswatun hasanah or good role models for students, provide advice on the importance of worship discipline, provide punishment for students who are not disciplined and give rewards to students who are disciplined in carrying out prayers. In addition, jurisprudence teachers also continue to conduct trainings and practices by continuing to be supervised so that students are accustomed to discipline in carrying out worship.